ProduksiI Brown’s Gas Hasil Elektrolisis H2O Dengan Katalis NaHCO3 - Marlina, Ena; Wahyudi, Slamet; Yuliati, Lilis (Jurnal Rekayasa Mesin, 2013)
This research is intended to investigate the effect of NaHCO3 (Natrium Bicarbonate) percentage on the performance of HHO (Brown’s Gas) production using electrolysis method. Performance of HHO production that was observed in this research were electric power that used for HHO production as well as rate and efficiency of HHO production. Electrolysis is decomposition of water molecules (H2O) into hydrogen and oxigen molecules (HHO) using electricity in an electrolite solution. This process takes place when two electrodes (anode and cathode) placed in the water and direct electric current flowed through the system. In this research Natrium Bicarbonate was dissolved in the water to increase the rate of electrolysis process. Percentage of Natrium Bicarbonate was varied from 2,5% – 15%. The results show that electric power that used for HHO production and rate of HHO production were increased with the increasing of Natrium Bicarbonate percentage and reach their maximum value at 12,5% Natrium Bicarbonat. However maximum value for electrolysis efficiency was occurred for Natrium Bicarbonate percentage of 10%.Keywords: Brown’s Gas, Electrolysis, NaHCO3 (Natrium Bikarbonate), Performance of electrolysis process